Frequency and Culture Sensitivity for Bacteremia During Febrile Neutropenia in Children with Acute Lymphoblastic Leukemia. Do Age and Gender Matter? - Bin Mehmood, Rana Usama; Aslam, Afra; Ayaz, Saeed Bin; Choudhry, Shehla; Javed, Sidra; Ashraf, Khaula (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To determine the frequency of bacteremia and its association with age and gender in febrile neutropenic children suffering from acute lymphoblastic leukemia and identify the commonest pathogens and their antibiotic susceptibility identified on blood cultures.Study Design: Cross-sectional analytical studyPlace and Duration of Study: Pediatrics Inpatient Department, Shifa International Hospital, Islamabad Pakistan, from Sep 2018 to Mar 2019.Methodology: Children with acute lymphoblastic leukemia aged 1-12 years, presenting with temperature >100ºF and absolute neutrophil count of